Pelatihan Pengajuan Nomor Induk Berusaha (NIB) Secara Online pada Forum UMKM Rawa Panjang, Kecamatan Bojonggede, Kabupaten Bogor - Elmira Siska; Nurlaela Eva Puji Lestari; Siti Mabrur Rachmah; Lela Elvira (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2024)
This community service activity (PKM) was carried out with partners, namely the Rawa Panjang UMKM Forum. The problem faced by the Rawa Panjang Village UMKM Forum is the lack of understanding and knowledge of the importance of business legality. Out of the 400 members, only around 40% have business legality. While the remaining 60% do not have business legality. This community service activity aims to improve the knowledge and expertise of partners in promoting NIB online on the official OSS (Online Single Submission) website. The implementation of PKM activities consists of three stages, namely the preparation, implementation, and evaluation stages. The recapitulation analysis shows that the material presented is in accordance with the needs of the partners. In addition, it shows that this training also has an impact on increasing the knowledge and expertise of members of the Rawa Panjang UMKM Forum